Justifying Priorities in Regional Development through an Integrated Assessment of a Region’s Overall Potential - Speshilova, Natalia; Nesedov , Pavel O. (Economy of Regions, 2026)
Uneven socio-economic development in Russian regions stems not from some regions lagging behind the leaders, but from inefficient and fragmented use of internal potential. This study offers a methodological approach to inform strategic regional development using a comprehensive assessment of a region’s potential. The analysis uses official statistical data from 2014 to 2023 and examines 87 indicators across 20 areas of regional development using classical analysis and synthesis. The proposed methodology assesses regional potential by accounting for neighbouring regions, population density, and interdependencies among indicators. An original matrix of inter-potential interactions is introduced to identify both limiting and enabling factors in regional economic performance. The methodology’s validity is supported by expert evaluation. It is applied to regions of the Volga Federal Okrug, with a particular focus on Orenburg Oblast, which is notable for its combination of agriculture, industry, extractive sectors, and border location. Comparison of the results with the region’s 2030 Development Strategy reveals gaps and priorities for investment, industry, R&D, and logistics. Analysis of regional growth drivers in relation to neighbouring regions also reveals potential for creating interregional specialized territories to enhance cooperation. The methodology has practical relevance for designing regional development strategies and policy programs. Due to the complexity of the calculations, digitalizing the evaluation algorithm is recommended. The findings can be of interest to state and municipal authorities.